Dinamika Jilbab dalam Sudut Pandang Sejarah: Dialog antara Budaya dan Agama - Nanang Sudiyono; Qurrota A’yun Isbachunuri; Nurul Mubin (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Wearing a hijab for Muslim women is not just a habit, but an obligation that has a deep meaning in religion and daily life. This tradition is not just owned by Muslims, in ancient times this tradition has been attached as a civilization, so it is important to explore this matter further. This article aims to trace the dynamics of the hijab from a historical perspective. With a qualitative descriptive approach, the study found that the history of wearing the hijab is much older than Islam. The use of the hijab has existed in various cultures and civilizations in the world, even before Islam was born, precisely since the Sumerian civilization in Mesopotamia around 5,000 BC. The tradition of the hijab is also found in ancient Assyrian society. Wearing the hijab can be a symbol of honor and social status, especially for elite women or priestesses, a differentiator between free women and slaves, and part of a particular cultural tradition, as seen in various ancient civilizations. Thus, wearing the hijab is not only a practice related to Islam, but also a social phenomenon that has existed for a long time in the history of human civilization. This finding is important for the creation of a dignified society, amidst the fading awareness of wearing the hijab among Muslim teenagers. This research provides a direction for future research on the importance of the hijab for the honor of women more specifically.